MATH SOLVE

3 months ago

Q:
# Need answer ASAP plz

Accepted Solution

A:

ANSWER[tex]x - 4 = 0 \: or \: x + 2 = 0[/tex]EXPLANATIONGiven:[tex](x + 1)(x - 3) = 5[/tex]Expand:[tex] {x}^{2} - 3x + x - 3 = 5[/tex][tex] {x}^{2} - 2x - 3 = 5[/tex]Equate everything to zero.[tex] {x}^{2} - 2x - 3 - 5 = 0[/tex][tex] {x}^{2} - 2x - 8 = 0[/tex]Split the middle term;[tex] {x}^{2} + 2x - 4x - 8 = 0[/tex]Factor;[tex] x(x + 2) - 4(x + 2) = 0[/tex][tex](x - 4)(x + 2) = 0[/tex]Use zero product property,[tex]x - 4 = 0 \: or \: x + 2 = 0[/tex]